Bread-derived carbon foam as an adsorbent for solid-phase microextraction of polybrominated diphenyl ethers. Issue 48 (30th November 2017) - Yu, Hao; Zhao, Yanfang; Yang, Lingxiao; Chen, Xiangfeng
Abstract : In this work, bread-derived carbon foam (CF) was synthesized and used as a sorbent for solid-phase microextraction (SPME) of pollutants from environmental water samples. Abstract : In this work, bread-derived carbon foam (CF) was synthesized and used as a sorbent for solid-phase microextraction (SPME) of pollutants from environmental water samples. CF fabricated with flour and yeast via fermentation and carbonization is stiff, light weight, high in specific area, and porous. SPME coupled with gas chromatography-negative chemical ionization mass spectrometry was developed for determining polybrominated diphenyl ethers from environmental samples. Under optimal conditions, the developed method showed high sensitivity with limits of detection of 0.25–2 ng L −1 and S/N = 3 : 1, good linearity ( R 2 > 0.98) in the concentration range of 1–500 ng L −1, and satisfactory extraction repeatability (RSD < 12%, n = 6) and recoveries (71.8–114.4%). Furthermore, tap, pond, snow, and river water samples were used to test the applicability of the developed method. The satisfactory analysis performance demonstrated that the bread-derived CF could be used as a green, safe, and efficient sorbent for SPME of pollutants from environmental water samples.